Genome-Wide Analysis of Host Responses to Four Different Types of Microorganisms in Bombyx Mori (Lepidoptera: Bombycidae). Issue 1 (5th July 2016) - Cheng, Tingcai; Lin, Ping; Huang, Lulin; Wu, Yuqian; Jin, Shengkai; Liu, Chun; Xia, Qingyou
Abstract: Several pathogenic microorganisms have been used to investigate the genome-wide transcriptional responses of Bombyx mori to infection. However, studies have so far each focused on one microorganism, and systematic genome-wide comparison of transcriptional responses to different pathogenic microorganisms has not been undertaken. Here, we surveyed transcriptional responses of B. mori to its natural bacterial, viral, and fungal pathogens, Bacillus bombyseptieus, B. mori nucleopolyhedrovirus (BmNPV), and Beauveria bassiana, respectively, and to nonpathogenic Escherichia coli, by microarray analysis. In total, the expression of 2, 436, 1, 804, 1, 743, and 912 B. mori genes was modulated by infection with B. bombyseptieus, BmNPV, B. bassiana, and E. coli, respectively. Notably, the expression of 620, 400, 177, or 165 of these genes was only modulated by infection with B. bombyseptieus, BmNPV, B. bassiana, or E. coli, respectively. In contrast to the expression of genes related to juvenile hormone synthesis and metabolism, that of genes encoding juvenile hormone binding proteins was microorganism-specific. Three basal metabolic pathways were modulated by infection with any of the four microorganisms, and 3, 14, 5, and 2 metabolic pathways were specifically modulated by infection with B. bombyseptieus, BmNPV, B. bassiana, and E. coli, respectively. Interestingly, BmNPV infection modulated the JAK/STAT signaling pathway, whereas both the Imd and Toll signaling pathways were modulated by infection with B. bombyseptieus, B. bassiana, or E. coli . These results elucidate potential molecular mechanisms of the host response to different microorganisms, and provide a foundation for further work on host–pathogen interaction.